Pengaruh Pelatihan Terhadap Kinerja Karyawan PT. Astra International, Tbk Daihatsu Cabang Malalayang - Gino E. Wuse; Sontje M. Sumayku; Roy F. Runtuwene (JURNAL ADMINISTRASI BISNIS, 2018)
Training is very important to be implemented because of the increasingly big business competition Pt. Astra International Tbk, Daihatsu Malalayang Branch needs to apply good training to every employee so that employees and companies are ready to compete with similar companies in the business world. The purpose of this training is to train the employees of PT. Astra International Tbk, Daihatsu Malalayang Branch. Analytical techniques used are scale scale, and simple linear regression using SPSS 13. The result of scale range analysis indicates that the training implementation is included in the criterion well with the average score of 85.94. The results of the working scale range analysis included in the high criterion with an average score of 40.60. Results of a simple linear regression study that has been done shows there is a significant influence between training variables and employee performance variables, can be seen in the correlation coefficient of 0.855 which means having a perfect relationship. While the hypothesis test results t arithmetic = 11.435 greater than t table = 1.677 This means Ho is rejected and Haimaan, then training has a positive effect on employee performance at PT. Astra International Tbk, Daihatsu Branch Malalayang thus hypothesized in Chapter I that "If training is done properly, then employee performance will increase", is acceptable.Keywords: Training, Employee Performance